POLA PENANGANAN KASUS PERCERAIAN DI KANTOR URUSAN AGAMA KECAMATAN NGUNUT KABUPATEN TULUNGAGUNG - Azizah, Rina Nur (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2017)
The marriage of a great event in the life of a human being between a man and a woman to live together concerning the bond as husband and wife with the aim of forming a family (household) were happy and conserved in order to worship and bertaqarrub Ilallah and follow the Sunnah of Rasul's to bring up a happy home prosperous, sakinah, mawaddah, warahmah institutions to create good human generation, which is blessed by Allah SWT.This research was motivated by the occurrence of divorce cases in the Office of Religious Affairs Ngunut Tulungagung subdistrict, how the pattern of handling divorce cases in the District Office of Religious Affairs Ngunut well as factors that support and hinder handling divorce cases in the Office of Religious Affairs Ngunut Tulungagung subdistrict.The method used is descriptive research with a qualitative approach where the focus of research conducted at the Office of Religious Affairs District of Ngunut Tulungagung which has been mentioned in the Marriage Act that divorce can only be done in the Religious Court after the court concerned to try and not succeed reconcile the two sides.The results of research in the can is, the pattern of handling divorce cases in order to improve public services which include registration of marriages, Adviser husband and wife who were at loggerheads conducted by BP4 (Advisory Board, Marriage, Dispute and Divorce) as well as recording a pledge of divorce and break up divorce dap at said handling quite well when based on fewer and fewer complaints from the public regarding the service delivered to KUA Ngunut Tulungagung subdistrict.PPN officer can only monitor and record the marriage as well as informing refer only, while the process of divorce and accountable only to do a hearing of the Religious Court.Factors that become an obstacle in handling divorce cases is the lack of public understanding about the rules and regulations, especially laws on marriage.